Mixed methods pilot evaluation of interpersonal psychotherapy for body image for adolescents. (January 2021) - Duffy, Fiona; Sharpe, Helen; Beveridge, Emily; Osborne, Kate; Richards, Cathy
Body dissatisfaction is common in adolescence and associated with poor outcomes. The aim of this mixed method pilot evaluation was to determine acceptability, feasibility and preliminary efficacy of Interpersonal Psychotherapy for Body Image (IPT-BI), a school-based group intervention for young people with high levels of body dissatisfaction. Eighteen participants (11–13 years, 78% female) took part in two IPT-BI groups ( n  = 10; n  = 8). Feasibility was measured by recruitment and attrition rates; acceptability using a treatment satisfaction questionnaire and focus groups; and clinical outcomes at baseline, each session and post intervention. The majority of young people (72%, n  = 18/25) who were referred or expressed interest went on to take part. Average session attendance was 100% and 89%. Participants expressed high levels of treatment satisfaction with 94% ( n  = 16/17) rating IPT-BI as 'quite helpful' or 'very helpful' and 94% ( n  = 16/17) stating they would recommend it to others. Preliminary exploration of efficacy showed significant improvements in body image and significant reductions in interpersonal difficulties and appearance-based conversations. Young people valued specific IPT-BI skills (role play, communication strategies), alongside generic therapeutic factors (therapeutic alliance, group cohesion). IPT-BI is feasible and acceptable with promising provisional clinical outcomes indicating the need for a fully powered randomised controlled trial.